2013
DOI: 10.1002/job.1914
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary retirement, bridge employment, and satisfaction with life: A longitudinal investigation

Abstract: Summary The increased popularity of bridge employment has raised questions about its consequences for well‐being in late adult life. This research explored the consequences of bridge employment for the level of life satisfaction of older adults during the retirement transition period. Changes in life satisfaction were considered to be a function of the different intentions and motives for taking bridge jobs. Furthermore, the impact of bridge employment was empirically examined conditional on the voluntariness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 52 publications
3
123
0
12
Order By: Relevance
“…Examining intentions in addition to behavior can, however, be expected to result in a more comprehensive understanding of the way in which women's retirement processes are embedded in the family life course. Prior studies have shown that a considerable share of retirement transitions (around 25-30 percent) is perceived as involuntary or forced (Dingemans and Henkens 2014;Szinovacz and Davey 2005;Van Solinge and Henkens 2007), suggesting that control over the retirement transition is often limited. Therefore, experiences earlier in life might be more informative for explaining differences in retirement intentions than for explaining differences in retirement behavior (Beehr 1986).…”
Section: Issues By Examining the Following Research Question: To Whamentioning
confidence: 99%
“…Examining intentions in addition to behavior can, however, be expected to result in a more comprehensive understanding of the way in which women's retirement processes are embedded in the family life course. Prior studies have shown that a considerable share of retirement transitions (around 25-30 percent) is perceived as involuntary or forced (Dingemans and Henkens 2014;Szinovacz and Davey 2005;Van Solinge and Henkens 2007), suggesting that control over the retirement transition is often limited. Therefore, experiences earlier in life might be more informative for explaining differences in retirement intentions than for explaining differences in retirement behavior (Beehr 1986).…”
Section: Issues By Examining the Following Research Question: To Whamentioning
confidence: 99%
“…Retirement increasingly contains post-retirement transitions in and out of the workforce, often referred to as "bridge employment" (4). Nonetheless, while the mental well-being of retirees has been examined in relation to retirement voluntariness (5,6) and bridge employment (7), few studies have thus far focused on the combined impact of these retirement transition characteristics (8).…”
mentioning
confidence: 99%
“…La práctica privada pasa a perfilarse como un complemento económico y una forma de protegerse y compensar. Esto significa una no-ruptura del ámbito laboral a través de un "trabajo-puente" que presenta efectos muy positivos para el profesional, tal y como se ha señalado en otras investigaciones 7,20,26 . Este "trabajo-puente", que no es homogéneo para todo el colectivo, supone un espacio para seguir siendo médico y compensar los efectos de la presión o la ignorancia institucional.…”
Section: Categoríaunclassified